2017
DOI: 10.3892/mmr.2017.6395
|View full text |Cite
|
Sign up to set email alerts
|

Deep vein thrombosis related to environment

Abstract: The first-time venous thromboembolism (VTE) is less frequent than other thrombotic events, however, both the pulmonary embolism (PE) and the deep vein thrombosis (DVT) show a frequent morbidity. Many factors play as risk situations in determining VTE, and the air exposure to the fine and ultrafine particulate matter (PM) as PM10, PM2.5, PM0.1 is considered. Epidemiological studies have supported this association although both the effective burden of the association and the mechanisms are to date unclear. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Exposure to PM has been shown to induce a prothrombotic state, which may play a role in its ability to cause arterial thrombotic (myocardial infarction, ischemic/thrombotic cerebrovascular events) and venous thrombotic events (deep venous thrombosis) ( 81 , 82 ). Exposure to PM induces the production of fibrinogen, and other factors that play a role in hemostasis including Von Willebrand factor, sCD62P, and sCD40L ( 65 , 83 85 ).…”
Section: Exposure To Pm and Cardiovascular Diseasementioning
confidence: 99%
“…Exposure to PM has been shown to induce a prothrombotic state, which may play a role in its ability to cause arterial thrombotic (myocardial infarction, ischemic/thrombotic cerebrovascular events) and venous thrombotic events (deep venous thrombosis) ( 81 , 82 ). Exposure to PM induces the production of fibrinogen, and other factors that play a role in hemostasis including Von Willebrand factor, sCD62P, and sCD40L ( 65 , 83 85 ).…”
Section: Exposure To Pm and Cardiovascular Diseasementioning
confidence: 99%
“…long-term inflammation. Signorelli et al (2017) stated that air pollution and inhalation of PM 10 , PM 2.5 and PM 1 play an important role in DVT, PE, and VTE (Signorelli et al, 2017). Emmerechts et al (2012) studied the relation between PM and VTE in Belgium and found that VTE was associated with long-term exposure to air pollution (Emmerechts et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The factors that can cause DVT include pregnancy, the use of contraceptives, and the use of estrogen hormones to reduce the symptoms of menopause ( Benjamin et al., 2017 ). However, according to some recent studies exposure to polluted air ( Baccarelli et al., 2008 ; Dales et al., 2010 ; Kloog et al., 2015 ; Signorelli et al., 2017 )might be the cause of DVT as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the platelet aggregation rate of thrombosis patients is increased. In the study conducted by Signorelli et al , it was suggested that the platelet aggregation activity of patients with deep vein thrombosis of lower extremity is enhanced ( 15 ). By analyzing the expression of the three substances (PAF, CD62p, and CD63) in the two groups, it was found that the expression levels of the three substances were significantly higher in postpartum deep vein thrombosis patients than in subjects with normal recovery.…”
Section: Discussionmentioning
confidence: 99%